Corpora Galore: Analyses and Techniques in Describing English. (Language and Computers: Studies in Practical Linguistics 30.). - Pahta, Päivi (Literary & Linguistic Computing, 2001)
The article reviews the book "Corpora Galore: Analyses and Techniques in Describing English," edited by John M. Kirk.